The Role of Artificial Intelligence in Arbitration and Legal Challenges Arising from Automated Decisions in Sports - Farajpour, Reza; Amerinia, Mohammad Bagher; Pourjavaheri , Ali (AI and Tech in Behavioral and Social Sciences, 2025)
The integration of artificial intelligence (AI) into sports arbitration has become increasingly prominent in recent years. Technologies such as the Video Assistant Referee (VAR) in football, Hawk-Eye in tennis, and various video analysis systems in basketball and baseball have enhanced the precision of officiating. However, the widespread adoption of these technologies has also introduced significant legal and ethical dilemmas. One of the primary concerns is the issue of legal liability in cases of erroneous AI-driven decisions. If an athlete or team suffers due to an AI-related error, determining accountability becomes a challenge. Furthermore, the extent to which clubs and athletes can contest these decisions remains a critical question. Another key challenge involves the transparency of AI-based decision-making processes. Many sports arbitration algorithms are developed by private entities, and their inner workings are often undisclosed. This opacity can hinder athletes and teams from effectively appealing disputed decisions, raising concerns about fairness in sports governance. Moreover, AI’s influence on the traditional role of human referees is a subject of ongoing debate. While AI systems are capable of delivering rapid and highly accurate judgments, they may lack the ability to assess contextual elements of the game, players’ intent, and other human factors. This study explores the legal, ethical, and operational challenges associated with AI-driven sports arbitration. It proposes regulatory frameworks for establishing accountability and analyzes contentious decisions made by technologies such as VAR and Hawk-Eye. The findings aim to support sports policymakers, legal professionals in sports law, and international governing bodies in formulating comprehensive guidelines for the ethical and effective use of AI in officiating.